2010
DOI: 10.3390/molecules15129008
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Properties and Mechanism of Action of Gynura procumbens Water Extract in Streptozotocin-Induced Diabetic Rats

Abstract: Gynura procumbens (Lour.) Merr (family Compositae) is cultivated in Southeast Asia, especially Indonesia, Malaysia and Thailand, for medicinal purposes. This study evaluated the in vivo hypoglycemic properties of the water extract of G. procumbens following 14 days of treatment and in vitro in RIN-5F cells. Glucose absorption from the intestines and its glucose uptake in abdominal skeletal muscle were assessed. The antidiabetic effect of water extract of G. procumbens leaves was investigated in streptozotocin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 17 publications
2
84
0
2
Order By: Relevance
“…Zurina et al (2010) reported that different methods of plant extraction resulted in different outcome. It was found that 25% ethanolic extract of Gynura procumbens gave the best result in reducing blood glucose level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zurina et al (2010) reported that different methods of plant extraction resulted in different outcome. It was found that 25% ethanolic extract of Gynura procumbens gave the best result in reducing blood glucose level.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 25% ethanolic extract of Gynura procumbens gave the best result in reducing blood glucose level. It was also found that the Gynura procumbens extract mimics the metformin mechanism (Algariri et al 2013) by increasing the glucose intake in the muscle cells (Zurina et al 2010). However, its potential in fertility on diabetic subjects remains hardly known.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Akowuah et al on the contrary indicated its glucose lowering effect in normal rats [4] . In the most recent study, the extract of G. procumbens was reported to produce significant elevation in the fasting blood glucose (FBG) levels of normal rats, but a decrease in diabetic rats [5] . There is a basic need to stream line these reports, given the widespread traditional use of G. procumbens.…”
Section: Commentsmentioning
confidence: 99%
“…Zhang and Tan (2000) discovered that leaf extracts of G. procumbens significantly suppressed the level of elevated serum glucose, and reduced serum cholesterol and triglyceride levels in diabetic rats. Akowuah et al (2002) and Hassan et al (2010) showed significant hypoglycaemic effect of G. procumbens leaf extracts in streptozotocin-induced diabetic rats. In addition, Akowuah et al (2002) isolated flavonol glycosides (e.g.…”
Section: Introductionmentioning
confidence: 99%